2015
DOI: 10.1111/anae.13330
|View full text |Cite
|
Sign up to set email alerts
|

A randomised comparison of the Ambu® AuraGain and the LMA® supreme in infants and children

Abstract: SummaryWe conducted a randomised trial in 100 children in order to compare the clinical performance of the Ambu â AuraGain TM and the LMA â Supreme * for airway maintenance during mechanical ventilation. The primary outcomes were initial and 10-min airway leak pressures. Ease, time and success rates for device and gastric tube insertion, fibreoptic grades of view, airway quality during anaesthetic maintenance, and complications were also assessed. 16-26 [12-40]) cmH 2 O, p = 0.08, respectively. Ease, time and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
73
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(89 citation statements)
references
References 23 publications
7
73
2
3
Order By: Relevance
“…[9] Another study reports similar OLP of AAU and LMA Supreme™ in children during controlled ventilation under general anaesthesia. [10] However, the OLP of AAU was comparable to that of other SGAs such as i-gel, PLMA and LMA Supreme™ as reported in some other studies. [81213] In our study, the OLP of both AAU and PLMA was higher than the peak airway pressure and was sufficient to prevent aspiration while ventilating the study patients during carboperitoneum.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…[9] Another study reports similar OLP of AAU and LMA Supreme™ in children during controlled ventilation under general anaesthesia. [10] However, the OLP of AAU was comparable to that of other SGAs such as i-gel, PLMA and LMA Supreme™ as reported in some other studies. [81213] In our study, the OLP of both AAU and PLMA was higher than the peak airway pressure and was sufficient to prevent aspiration while ventilating the study patients during carboperitoneum.…”
Section: Discussionsupporting
confidence: 78%
“…AAU has been compared to LMA supreme in a few studies,[91011] but to the best of our knowledge, there is no literature available that compares the clinical efficacy of AAU to PLMA in laparoscopic cholecystectomy. Hence, this study was undertaken to evaluate the safety profile of AAU in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…The full texts of 118 articles were examined in detail. We included 65 articles in this network meta‐analysis (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…The trials had a median (range [IQR]) sample size of 60 (27–240 [53–100]). Sevoflurane was administered for anaesthesia induction in 44 studies . There were eight crossover designed studies .…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, various studies have been done on device performance and insertion parameters for this device, [15,16,17] but no study has been reported so far comparing the effect of insertion or removal of Ambu AuraGain on IOP.…”
Section: Discussionmentioning
confidence: 99%